Pengaruh Pembelajaran Demonstrasi Interaktif terhadap Keterampilan Proses Sains Dasar Siswa SMA pada Materi Perubahan Lingkungan - Noviani, Dwi Rahayu Lestari (Assimilation: Indonesian Journal of Biology Education, 2019)
The achievement of students science process skills in Indonesia is relatively low, this is partly because learning has not yet explored and facilitated students science process skills. This study aims to identify the effect of interactive demonstrations to basic science process skills of senior high school students in environmental change concept, with global warming sub concept. The subjects of this study were X grade of science in second semester, academic year 2017/2018. The method used in this research was quasi experiment with non equivalent pre-test post-test control group design. The research data was collected by using basic science process skills test, observation form, and questionnaire. The results of data analysis using the Mann Whitney test with a significance level of 0,05 to the value of the post-test of basic science process skills showed a significant difference in basic science process skills of students between experimental group and control group. N-gain of basic science process skills in the experimental group is 0,56, while in the control group is 0,43. Improved basic science process skills in the experimental group and control group are in the medium category. Neverthless, the average of N-gain in the experimental group is higher than the control group. The results of this study indicate that 97,5% of learning activities performed well. Based on the results of the research, it can be concluded that the interactive demonstrations learning trains to improve students basic science process skills.